Analysis of Road Damage Levels Using the Surface Distress Index Method and Handling Cracked Roads - Haldiana, Haldiana; Nanang Prayudyanto, Muhamad; Rulhendri, Rulhendri (Universitas Ibn Khaldun Bogor, 2024)
Analysis of the Level of Road Damage Using the Surface Distress Index Method and Evaluation and Handling of Cracked Roads (Case Study: Jalan Ciherang Cutak-Jalan Suka Mulya, Ciomas District, Bogor Regency. The existence of roads is very necessary to support the rate of agricultural and other economic growth, considering the important benefits So the road construction and maintenance sector is a priority for research and development in planning, implementation and maintenance. The road sections experienced damage which includes several factors such as road sections that are frequently used, poor drainage channels. The aim of this research is to determine the type of damage, evaluate and handle damage to road sections, as well as obtain damage values on Jalan Ciherang Cutak-Jalan Suka Mulya, Ciomas District, Bogor Regency based on the parameters of the Surface Distress Index (SDI) method. The length of the road used in this research is ± 1000m which is divided into 10 segments with The length of each road is ± 100m. In this research the author used the Surface Distress Index (SDI) method and used data on damage dimensions including length, width and depth of damage. Based on the results obtained, there are 4 types of damage found on the Jalan Ciherang Cutak-Jalan Suka Mulya section, Ciomas District, Bogor Regency, namely: pavement edge defects, potholes, alligator cracks, longitudinal cracks and the results of the percentage of SDI values in the average damage. The average is 34, which states that the Jalan Ciherang Cutak-Jalan Suka Mulya section, Ciomas District, Bogor Regency is in good condition, and there is an evaluation and handling of SDI values on the Ciherang Cutak-Jalan Suka Mulya road, the road is in segments 1-4,8-10 with good condition. while 5 and 7 are in moderate condition, but in segment 7 there is a high damage area value, namely 12.2%, so that widespread cracks do not occur, routine and periodic maintenance is needed along the Ciherang Cutak Suka Mulya road so that the damage does not spread.